Discrepancies Between Quarterly GDP Estimates - Bloem, Adriaan (Washington, D.C. : International Monetary Fund, 1997)
Countries compiling quarterly estimates for gross domestic product (GDP) often use alternative approaches simultaneously. This may result in the publication of different measures of quarterly GDP and discrepancies between these measures. Such discrepancies are unavoidable, unless reconciliation takes place or the measures are mutually interdependent. This paper examines international practices in this respect, focusing on OECD member countries that publish quarterly GDP data. Of these, five publish GDP data with discrepancies-the United States, the United Kingdom, Canada, Australia, and New Zealand-and the paper examines causes and the development of these discrepancies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet